A Development of E-Learning Chemistry Based on Project Based Learning on Buffer Solution Using Then Flipped Classroom Approach in Class XI SMA/MA - Karmila, Aroma; Arief, Nor Adila Rosli; Friska, Shintia; Astuti, Leli (INTERNATIONAL JOURNAL OF HIGH INFORMATION, COMPUTERIZATION, ENGINEERING AND APPLIED SCIENCE (JHICE), 2022)
Abstract—This development research aims to produce a development product in the form of E learning based on Project Based Learning (PPA) with a valid Flipped Classroom approach in SMA / MA. This study uses a 4-D model development research design which includes defining, designing, developing and distributing. The product validity test was carried out by collecting data from three validators (high school chemistry teachers) using an instrument in the form of a validation questionnaire. Based on the qualitative descriptive analysis using the formula "Aiken, the results for construct validation are 0.86 and content validation is 0.86. Based on the results and discussion, it is concluded that E-learning based on Project Based Learning (PPA) with the Flipped Classroom approach in SMA / MA that is valid is categorized as valid.